2020
DOI: 10.35568/abdimas.v3i2.458
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayaan Kelompok Remaja dalam Pencegahan Perilaku Bullying di SMA X Baros Serang Banten

Abstract: Bullying merupakan perilaku agresif yang mengakibatkan tekanan pada pihak yang lebih lemah sehingga korban tidak mampu untuk membela dan mempertahankan dirinya. Selain itu penting untuk diperhatikan adalah bukan sekedar tindakan yang dilakukan, tetapi dampak tindakan tersebut bagi korban. Bullying dapat mengubah suasana sekolah yang awalnya menyenangkan, belajar sambil berteman, menjadi menakutkan bahkan mimpi buruk. perilaku bullying memiliki dampak negatif di segala aspek kehidupan. Tujuan pelaksanaan progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Adolescents experience problems that can hinder their psychological growth and development and contribute to the formation of their self-concept, so that there is a risk of adolescent self-confidence to face the future. Based on the results of community service activities (Novianti, 2020) it was found that there was an increase in the ability to find good friends, recognize problems that might arise in friendship and how to speak assertively. (Novianti & Tobing, 2020) Islamic boarding schools are one form of community activity in the religious path that plays an important role in the development of human resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents experience problems that can hinder their psychological growth and development and contribute to the formation of their self-concept, so that there is a risk of adolescent self-confidence to face the future. Based on the results of community service activities (Novianti, 2020) it was found that there was an increase in the ability to find good friends, recognize problems that might arise in friendship and how to speak assertively. (Novianti & Tobing, 2020) Islamic boarding schools are one form of community activity in the religious path that plays an important role in the development of human resources.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of community service activities (Novianti, 2020) it was found that there was an increase in the ability to find good friends, recognize problems that might arise in friendship and how to speak assertively. (Novianti & Tobing, 2020) Islamic boarding schools are one form of community activity in the religious path that plays an important role in the development of human resources. Poskestren (Pesantren Health Center) is a form of community empowerment in Islamic boarding schools which is a facilitation effort, with the aim that the residents of Islamic boarding schools know and understand the health problems they face, and are expected to plan and make efforts to solve them by utilizing the potential according to the situation, conditions and conditions.…”
Section: Introductionmentioning
confidence: 99%